Dietary heat‐killed Lactobacillus brevis SBC8803 (SBL88™) improves hippocampus‐dependent memory performance and adult hippocampal neurogenesis - Rie Ishikawa; Hotaka Fukushima; Yasukazu Nakakita; Hisao Kado; Satoshi Kida (Neuropsychopharmacology Reports, 2019)
Abstract Aims Lactobacillus species are used widely as various food and supplements to improve health. Previous studies have shown that heat‐killed Lactobacillus brevis SBC8803 induces serotonin release from intestinal cells and affects sleep rhythm and the autonomic nervous system. However, the effect of SBC8803 on cognitive function remains unknown. Here, we examined the effects of dietary heat‐killed SBC8803 on hippocampus‐dependent memory and adult hippocampal neurogenesis. Methods Hippocampus‐dependent memory performance was assessed in mice fed heat‐killed SBC8803 using social recognition and contextual fear conditioning tasks. Adult hippocampal neurogenesis was evaluated before, during, and after feeding heat‐killed SBC8803 by measuring the number of 5‐bromo‐2‐deoxyuridine (BrdU)‐positive cells following systemic injections of BrdU using immunohistochemistry. Results Mice fed a heat‐killed SBC8803 diet showed an improvement of hippocampus‐dependent social recognition and contextual fear memories and enhanced adult hippocampal neurogenesis by increasing the survival, but not proliferation, of newborn neurons. Conclusion Dietary heat‐killed SBC8803 functions as memory and neurogenesis enhancers.